2020
DOI: 10.1212/wnl.0000000000010468
|View full text |Cite
|
Sign up to set email alerts
|

Association of fast ripples on intracranial EEG and outcomes after epilepsy surgery

Abstract: ObjectiveTo examine if fast ripples (FRs) are an accurate marker of the epileptogenic zone, we analyzed overnight stereo-EEG recordings from 43 patients, and hypothesized that FR resection ratio, maximal FR rate, and FR distribution predict postsurgical seizure outcome.MethodsWe detected FRs automatically from an overnight recording edited for artefacts and visually from a 5-minute period of slow-wave sleep. We primarily examined the accuracy of removing ≥50% of total FR events or of channels with FRs to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…Among the 8 patients with post-operative MRI, fRonO had the highest accuracy for localizing the EZ, which is consistent with many past studies relating resection of HFOs with outcome 4 , 6 , 7 , 15 , 32 , 54 , 55 . By contrast, fRonO rates had the lowest accuracy of all the HFO types for identifying the SOZ in both intraoperative and sleep recordings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Among the 8 patients with post-operative MRI, fRonO had the highest accuracy for localizing the EZ, which is consistent with many past studies relating resection of HFOs with outcome 4 , 6 , 7 , 15 , 32 , 54 , 55 . By contrast, fRonO rates had the lowest accuracy of all the HFO types for identifying the SOZ in both intraoperative and sleep recordings.…”
Section: Discussionsupporting
confidence: 88%
“…One contentious issue is whether the spatial distribution of HFO rates during non-REM sleep is stable 15 , 30 , 31 . One recent large study found that the classification accuracy of fast ripples for the EZ was higher when a full night of non-REM sleep was analyzed as opposed to 5-min segments 32 . This issue is of particular importance to comparing intraoperative to sleep recordings, since the duration of the intraoperative recordings are intrinsically limited.…”
Section: Introductionmentioning
confidence: 99%
“…According to the EZ theory, if the EZ and SOZ are discordant, then a resection that targets the SOZ should result in little to no improvement in post-operative seizure outcome (Figure 1A). We used rates of HFO as a proxy for the EZ 24, 26, 27, 30, 31, 69, 70 to test the hypothesis that there is less overlap of EZ with the SOZ in non-responders than in responders. We calculated receiver operating characteristic (ROC) curves for each HFO subtype and sharp-spikes (Figure 1B) rates in classifying the SOZ for each of the patient cohorts (Figure 2A-E).…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence rate of FRs recorded on clinical macroelectrodes depends on vigilance states, showing the highest incidence during sleep 18 . Here, we asked whether FRs detected on micro-wires were also modulated by vigilance states at a fine temporal resolution.…”
Section: Resultsmentioning
confidence: 99%